2021
DOI: 10.1115/1.4051887
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emission Analysis of Integrated Production-Inventory-Transportation Supply Chain Enabled by Additive Manufacturing

Abstract: Additive manufacturing (AM), owing to its unique layer-wise production method, can offer evident advantages comparing to traditional manufacturing (TM) technologies such as faster production, lower cost, and less waste. The uses of AM in rapid tooling, prototyping, and manufacturing have been innovating the current manufacturing industry from the process level to the entire supply chain. Most existing research on AM is focused on process improvement and new materials, largely neglecting the potential economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Sun et al (2021) reported that the AM processes and printed products must be validated and qualified to satisfy the standards of critical parts in energy production (e.g., nuclear energy, oil and gas), conversion, and storage systems (e.g., battery and fuel cell). Di and Yang (2022) investigated the economic and environmental benefits of the integrated production–inventory–transportation (PIT) supply chain structure and suggested that this structure enabled by AM allows a reduction of approximately 26% of greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al (2021) reported that the AM processes and printed products must be validated and qualified to satisfy the standards of critical parts in energy production (e.g., nuclear energy, oil and gas), conversion, and storage systems (e.g., battery and fuel cell). Di and Yang (2022) investigated the economic and environmental benefits of the integrated production–inventory–transportation (PIT) supply chain structure and suggested that this structure enabled by AM allows a reduction of approximately 26% of greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 99%